Signatures of Adaptation, Constraints, and Potential Redundancy in the Canonical Immune Genes of a Key Pollinator. (12th April 2023) - Larragy, Sarah J; Möllmann, Jannik S; Stout, Jane C; Carolan, James C; Colgan, Thomas J
Abstract: All organisms require an immune system to recognize, differentiate, and defend against pathogens. From an evolutionary perspective, immune systems evolve under strong selective pressures exerted by fast-evolving pathogens. However, the functional diversity of the immune system means that different immune components and their associated genes may evolve under varying forms of selection. Insect pollinators, which provide essential ecosystem services, are an important system in which to understand how selection has shaped immune gene evolution as their populations are experiencing declines with pathogens highlighted as a potential contributing factor. To improve our understanding of the genetic variation found in the immune genes of an essential pollinator, we performed whole-genome resequencing of wild-caught Bombus terrestris males. We first assessed nucleotide diversity and extended haplotype homozygosity for canonical immune genes finding the strongest signatures of positive selection acting on genes involved in pathogen recognition and antiviral defense, possibly driven by growing pathogen spread in wild populations. We also identified immune genes evolving under strong purifying selection, highlighting potential constraints on the bumblebee immune system. Lastly, we highlight the potential loss of function alleles present in the immune genes of wild-caught haploid males, suggesting that such genes are potentially less essential for development and survival and represent redundancy in the gene repertoire of the bumblebee immune system. Collectively, our analysis provides novel insights into the recent evolutionary history of the immune system of a key pollinator, highlighting targets of selection, constraints to adaptation, and potential redundancy.